2007
DOI: 10.1111/j.1742-1241.2007.01505.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and marijuana smoking

Abstract: Marijuana is the most commonly used illicit drug while its abuse and dependence has an increasing prevalence among the young population. Marijuana smoking affects the circulatory system triggering various cardiovascular events. Of note, recent case reports indicate a possible association with atrial fibrillation (AF). In this article, we provide a brief systematic review of all reported cases implicating marijuana smoking in AF development and we concisely discuss the potential underlying mechanisms as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 27 publications
0
46
0
2
Order By: Relevance
“…No patient had a structural heart disease, and only one had a precipitating factor (hypertension); all patients had a favorable outcome with no recurrence after cessation of marijuana smoking [42]. Of note, adrenergic stimulation and disturbances in atrial coronary or microvascular flow associated with marijuana smoking may facilitate AF development and perpetuation possibly because of increased pulmonary vein ectopy, enhanced atrial electrical remodeling, and increased dispersion of refractoriness [42]. It should also be stressed that although this adverse event seems to be quite "benign" in young healthy subjects, it is apparently more "malignant" in older patients having other risk factors for thromboembolism.…”
Section: Increase In Sympathetic Activitymentioning
confidence: 95%
See 1 more Smart Citation
“…No patient had a structural heart disease, and only one had a precipitating factor (hypertension); all patients had a favorable outcome with no recurrence after cessation of marijuana smoking [42]. Of note, adrenergic stimulation and disturbances in atrial coronary or microvascular flow associated with marijuana smoking may facilitate AF development and perpetuation possibly because of increased pulmonary vein ectopy, enhanced atrial electrical remodeling, and increased dispersion of refractoriness [42]. It should also be stressed that although this adverse event seems to be quite "benign" in young healthy subjects, it is apparently more "malignant" in older patients having other risk factors for thromboembolism.…”
Section: Increase In Sympathetic Activitymentioning
confidence: 95%
“…In all instances, AF was of recent onset occurring shortly after marijuana smoking in young subjects. No patient had a structural heart disease, and only one had a precipitating factor (hypertension); all patients had a favorable outcome with no recurrence after cessation of marijuana smoking [42]. Of note, adrenergic stimulation and disturbances in atrial coronary or microvascular flow associated with marijuana smoking may facilitate AF development and perpetuation possibly because of increased pulmonary vein ectopy, enhanced atrial electrical remodeling, and increased dispersion of refractoriness [42].…”
Section: Increase In Sympathetic Activitymentioning
confidence: 98%
“…Czynniki ryzyka izolowanego AF wyst臋puj膮cego poni偶ej 60. roku 偶ycia s膮 s艂abiej udokumentowane. Rozwa偶ano wp艂yw u偶ywek (alkoholu, marihuany, palenia tytoniu), masy cia艂a, cech osobowo艣ci, aktywno艣ci fizycznej [2][3][4][5]. 呕adnego z powy偶szych czynnik贸w ryzyka nie stwierdzono u opisywanego pacjenta.…”
Section: Opis Przypadkuunclassified
“…Common cardiac manifestations of marijuana use include a dose-dependent tachycardia, hypotension, orthostatic hypotension, and a supine increase in blood pressure [2,3]. Cardiac arrhythmia including atrial fibrillation [4,5,6], atrial flutter [7], II degree AV block [8], ventricular fibrillation [9], ventricular tachycardia [10,11,12], asystole [13,14] have been reported with marijuana use.Despite these recent reports the effect of marijuana and its active components on ion-channels in general, cardiac ion channels in particular is largely lacking. Previous investigators have reported a case of acute marijuana intoxication that presented with Brugada like-ST segment elevation [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%